Analysis of serum albumin levels in pre and post hemodialysis among Chronic Renal Failure (CRF) patients at Dr. Wahidin Sudirohusodo Hospital, Makassar, Indonesia - Marini Kala Tanan; Fitriani Mangarengi; Mutmainnah Mutmainnah (Intisari Sains Medis, 2020)
Background: Chronic renal failure (CRF) is a clinical syndrome caused by a chronic decrease and gradual progression in kidney function. One of the complications of CRF can cause hypoalbuminemia. Hemodialysis can also cause hypoalbuminemia associated with inflammation and malnutrition due to loss of protein during dialysis. This study aims to analyze the albumin levels in pre and post hemodialysis CRF patients in Dr. Wahidin Sudirohusodo Hospital, Makassar.Methods: A retrospective study with cross sectional study design using secondary data obtained from the medical record was conducted among 50 patients at Dr. Wahidin Sudirohusodo Hospital, Makassar. Pre and post hemodialysis serum albumin levels of CRF patients from the Medical Record Installation were collected during September 2017 – 2018 period. Variables assessed in this study were gender, age, albumin levels, and the comparison of albumin levels based on gender. Data were analyzed using SPSS version 22 for Windows.Results: There were 52.0% male and 48.0% of female patients in this study. Most of the respondents were age 40-49 years old interval (30.0%). There was no significant difference in albumin levels between pre (3.07±0.63 g/dL) and post (3.05±0.54 g/dL) HD patients (p=0.665). Also, There was no significant difference in albumin levels in pre and post HD patients between male (p=0.434) and female (p=0.778).Conclusion: There were no significant differences between serum albumin levels pre and post hemodialysis in patients with CRF as well as based on gender.